Pengaruh Gaya Kepemimpinan, Motivasi dan Kompetensi Terhadap Kinerja Pegawai di Blud Rumah Sakit Umum Kota Banjar - Wawan Setiawan; Apri Budianto; Nana Darna (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to analyze the influence of leadership style, motivation, and competence on employee performance at the Regional Public Service Agency (BLUD) of Banjar City General Hospital. The problems raised include four main things: (1) the influence of leadership style on employee performance, (2) the influence of motivation on employee performance, (3) the influence of competence on employee performance, and (4) the influence of the combination of leadership style, motivation, and competence on employee performance. The method used is descriptive with data analysis through validity tests, reliability tests, descriptive statistics, and multiple regression analysis. The results of the study indicate that (1) leadership style has a positive effect on employee performance, (2) work motivation has a positive effect on employee performance, (3) competence has a positive effect on employee performance, and (4) increasing leadership style, motivation, and competence together can improve employee performance at BLUD RSU Banjar City.